Nightlife entertainment spots in cities as a potential criminogenic focus of sexual harassment - Bulovec, Tinkara (Varstvoslovje, 2020)
Purpose: The purpose of this paper is to illustrate the issue of sexual harassment, with a focus on nightlife entertainment areas in cities. It also presents the theoretical background, manifestation, and comprehensiveness of the phenomenon, as well as the victimological perspectives and some criminological interpretations. Design/Methods/Approach: A review of literature related to sexual harassment was conducted for the purpose of this paper, after which the method of deduction was applied to draw general findings with respect to the nightlife entertainment areas in cities. Findings: When reviewing the issue, it was found that the critical element for identifying diverse verbal, non-verbal and physical acts as sexual harassment stems from the fact that these acts are unsolicited and unwanted by the harassed individual. Sexual harassment occurs in all areas of human participation, either as part of domestic violence, in the workplace, in the context of education or in public places, where the nightlife (entertainment) areas in cities remain rather under-researched. The criminogenic potential of nightlife areas arises from, inter alia, the presence of alcohol and drugs in these areas, which contributes to the emergence of various types of deviant behaviours, including sexual harassment. Studies conducted abroad reveal that street harassment and stranger harassment represent an issue occurring in public places that, firstly, are not explicitly legally restricted. Secondly, they represent a form of sexual harassment, which is challenging to prove. Originality/Value: The paper focuses on providing an insight into the issue of sexual harassment in nightlife entertainment areas, which was deemed essential in terms of setting potential starting points for further discussion and research. Due to the theoretical nature of the paper, the findings can be used as a base for the empirical study of sexual harassment in nightlife entertainment spots in Slovenia.
Keywords: nightlife entertainment spots; območja nočnega življenja; sexual harassment; sexual violence; spolno nadlegovanje; spolno nasilje; street/stranger harassment; ulično spolno nadlegovanje; urban areas; urbano okolje